Aplicação de destilados provenientes do bio- óleo de pirólise de resíduos de gordura animal no asfalto diluído de petróleo - VALENTE, Alex Lopes (Universidade Federal do Pará, 2024)
Waste animal fats (WAF) can be converted into distillate fractions similar to petroleum solvents and used as biofuels or in other applications through pyrolysis and fractional distillation. The distillate fractions from the pyrolysis of triglycerides exhibit adequate viscosity and volatility compared to petroleum-derived fuels but show acid values between 60-140 mg KOH/g, preventing their direct use as biofuels without considerable purification of the distilled fractions. Diluted petroleum asphalt (DPA), used for priming soil in the construction of flexible pavement, requires adequate viscosity, volatility, and penetration, and the distillate fractions from WAF pyrolysis oil can be used as partial or full substitutes for the standard solvent (kerosene) in DPA production. The aim of this study was to test the compliance of DPAs prepared by substituting kerosene with bio-oil fractions from WAF according to DPA standards. First, WAF is obtained from meat waste through the rendering process. Then, WAF is subjected to pyrolysis in a semi-batch fixed-bed reactor (2L), and the resulting bio-oil is fractionally distilled into gasoline, kerosene, and diesel fractions. The pyrolysis process is analyzed concerning the type of reactor used, with a focus on the influence of temperature and reaction time, as well as the distillation profile. The distilled fractions are characterized by density, viscosity, and acid value before being used in the preparation of DPAs by partial and/or total (0-40% by weight) substitution of standard kerosene. The mixtures were tested for kinematic and Saybolt-Furol viscosity, flash point, and penetration, according to road pavement standards. The results showed that the kerosene and diesel fractions from WAF can be adequately used in the preparation of DPAs as a total substitute for the petroleum kerosene typically used.